Sadistic frenzy in Czech literature: Křesadlo, Zykmund, Urban - Pająk, Patrycjusz (Poznańskie Studia Slawistyczne, 2011)
In Czech literature of the second half of 20th century a sadistic frenzy is present in several few novels by Jan Křesadlo, Václav Zygmunt and Miloš Urban. Although Czech writers do not copy the work of Marquise de Sade, they do use the motif of sadism to diagnosis the human condition in modern times, just as he did. In his novels Gravelarks and The Lord of Castle Křesadlo comes back to the times of Czechoslovakian Stalinism. In the novel Graduates’ Jubilee Zykmund criticizes the middle-class mentality, while Urban, in his novel Michaela, depicts a world between fiction and reality. Czech authors present the sadistic frenzy as a synthesis of exclusivity and primitiveness. In this way they express the more general subject, that is the relationship between culture and nature in modern times. A more or less perceptible deformation of nature is a side-effect of human aspirations to rule over nature. The sadistic frenzy shows a extreme variant of this phenomenon.